2022
DOI: 10.1029/2022ms003132
|View full text |Cite
|
Sign up to set email alerts
|

ENSO‐GTC: ENSO Deep Learning Forecast Model With a Global Spatial‐Temporal Teleconnection Coupler

Abstract: El Niño-Southern Oscillation (ENSO) is one of the most dominant phenomena that modulate the global climate changes and varieties (Holton & Dmowska, 1989), the annual amplitudes of which usually derive significant impacts on social economy and human sustainability (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
(85 reference statements)
1
5
0
Order By: Relevance
“…In prior work, we have demonstrated that the Nonhomogeneous Hidden Markov Model (NHMM) applied to gridded, monthly SST data can objectively identify 5 ENSO flavors (whose spatial patterns and time of occurrence are similar to those of the 5 types of events typically identified), their temporal dynamics 24 , and their implications for global precipitation 23 . Further its 1-18 month ahead prediction skill for the benchmark Niño 3.4 index is comparable to that of other popular machine learning models 19,[25][26][27] . Given its interpretability and relative accuracy, we use it to explore how the temporal dynamics of ENSO may have changed relative to changing global temperature.…”
Section: Introductionsupporting
confidence: 56%
“…In prior work, we have demonstrated that the Nonhomogeneous Hidden Markov Model (NHMM) applied to gridded, monthly SST data can objectively identify 5 ENSO flavors (whose spatial patterns and time of occurrence are similar to those of the 5 types of events typically identified), their temporal dynamics 24 , and their implications for global precipitation 23 . Further its 1-18 month ahead prediction skill for the benchmark Niño 3.4 index is comparable to that of other popular machine learning models 19,[25][26][27] . Given its interpretability and relative accuracy, we use it to explore how the temporal dynamics of ENSO may have changed relative to changing global temperature.…”
Section: Introductionsupporting
confidence: 56%
“…Recently, deep learning (DL) methods have been widely applied to ENSO forecasts (Fang et al., 2022; Geng & Wang, 2021; Guo et al., 2020; Ham et al., 2019, 2021; Hassanibesheli et al., 2022; He et al., 2019; Mu et al., 2021, 2022; Nooteboom et al., 2018; Saha & Nanjundiah, 2020; Wang et al., 2021; Yan et al., 2020; Zhou & Zhang, 2023; Zhou et al., 2023). Among various DL models, the convolutional neural network (CNN)‐based models have achieved significant success in ENSO prediction.…”
Section: Introductionmentioning
confidence: 99%
“…ANNs have shown potential in capturing non-linear relationships intrinsic to ENSO (Ham et al 2019;Zhao and Sun 2022;Zhang et al 2022). Some studies employing recurrent neural networks and Convolutional Neural Networks (CNN) have achieved modest success in lead times ranging from 6 to 12 months and beyond, often outperforming traditional models (Mu et al 2021(Mu et al , 2022Liu et al 2023;Patil et al 2023;Wang and Huang 2023;Chen et al 2023a, b). Compared to traditional ANN and CNN, the combination of Autoencoders (AE) (Saha et al, 2020;Ibebuchi and Richman 2024) and Long Short-Term Memory Networks (LSTM) represent a viable novel alternative for ENSO prediction.…”
Section: Introductionmentioning
confidence: 99%